2021
DOI: 10.35699/2447-6218.2021.26317
|View full text |Cite
|
Sign up to set email alerts
|

Controle da dor em bovinos

Abstract: Com a crescente preocupação social quanto ao tratamento moral e ético dos animais de produção, o controle da dor em bovinos é um tema de grande relevância. Levando em consideração que os animais de produção são os que mais sofrem com a dor dentre os animais domésticos, faz-se necessário o desenvolvimento de estratégias e alternativas que minimizem o sofrimento e melhorem a qualidade de vida destes animais. É de extrema relevância conhecer as vias fisiopatológicas da dor, bem como classificá-las como adaptativa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
4

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 16 publications
0
3
0
4
Order By: Relevance
“…Social interactions analyzed in the first and second testing batteries recognized levels of hierarchy among rams from the same group and consistently identified the alpha ram. After orchiectomy, alpha rams had high USAPS scores, confirming the expected pain, as predicted by the preoperative analgesic half-life ( 23 ). However, alpha rams do not have reduced interest in the highly contestable feed resource in the presence of acute postoperative pain, rejecting our hypothesis.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Social interactions analyzed in the first and second testing batteries recognized levels of hierarchy among rams from the same group and consistently identified the alpha ram. After orchiectomy, alpha rams had high USAPS scores, confirming the expected pain, as predicted by the preoperative analgesic half-life ( 23 ). However, alpha rams do not have reduced interest in the highly contestable feed resource in the presence of acute postoperative pain, rejecting our hypothesis.…”
Section: Discussionmentioning
confidence: 65%
“…The instrument adopted to diagnose acute pain (USAPS) ( 17 ) in the present study indicated pain exclusively for alpha rams at the evaluation 8 h after orchiectomy, predicted to be the peak of postoperative pain due to the duration of the preoperative analgesia effect ( 23 ). Although the USAPS was initially developed and validated to assess abdominal pain induced by laparoscopy in female sheep, we suggest that the instrument was sensitive and specific enough to diagnose pain due to orchiectomy in rams.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Os anestésicos locais desempenham um papel crucial na administração de analgesia em animais de produção, garantindo a ausência de dor durante procedimentos cirúrgicos (Cortopassi et al, 2022;Massone, 2017;Muri et al, 2010). O mecanismo de ação desses anestésicos, como o cloridrato de lidocaína e o cloridrato de bupivacaína, envolve o bloqueio dos canais de sódio, impedindo a transmissão de impulsos nervosos e resultando na perda da sensação dolorosa (Amaral et al, 2018;Gaynor & Muir, 2009;Schade et al, 2021). No entanto, a eficácia desses anestésicos pode ser comprometida em tecidos inflamados ou infectados, nos quais o pH ácido interfere em seu funcionamento ideal.…”
Section: Discussionunclassified
“…A diversidade de PUBVET Doi: 10.31533/pubvet.v18n03e1556 técnicas de administração, como anestesia infiltrativa, bloqueio perineural, anestesia regional e bloqueio de Bier, oferece opções aos veterinários. A escolha do método depende da região que necessita de anestesia (Gaynor & Muir, 2009;Schade et al, 2021).…”
Section: Discussionunclassified